Три болючі втрати українського народознавства Словаччини - Мушинка М. (Народна творчість та етнографія, 2007)
This article is dedicated to the memory of three Ukrainian-Slovak cultural activists, scholars who played a great role in the development of the Ukrainian studies abroad: Mykhailo Molnar (who was Slovakian-Ukrainian literary critic and folklorist of the after-War period), Pavlo Markovych (famous painter and folk art researcher), Vikentiy Fedor (musician, pedagogue, and the organizer of the amateur folk music groups).